Implementasi Pendekatan Saintifik Pada Lingkungan Sekitar Dalam Membentuk Karakter Siswa Sekolah Dasar di Martapura Kalimantan Selatan - Rusdiyana Rusdiyana (Program of Biology Education, Universitas Lambung Mangkurat, 2019)
This study aims to identify the implementation of a scientific approach in the surrounding environment to build the students character of elementary school in Martapura, South Kalimantan. This type of research is quantitative research with survey method. The research population is all elementary school teachers in Martapura city. The research sample from 24 public teachers in 4 elementary schools who had implemented the 2013 curriculum. Data collection techniques used questionnaires and observations. The questionnaire was used to measure the results of the implementation of the scientific approach in shaping the character of elementary school students. Observations by means of visiting class sampling were carried out on 4 elementary school teachers. The data analysis technique used is descriptive analysis. The results of research on the implementation of a scientific approach to the surrounding environment in shaping the character of elementary school students averaged 82.53 with a good category. The results of observations on 4 teachers obtained an average score of 87.50 with a good category and the results of observations in 4 classes obtained an average score of student characters of 82.64 with a good category.